ART adherence and viral suppression are high among most non‐pregnant individuals with early‐stage, asymptomatic HIV infection: an observational study from Uganda and South Africa. Issue 2 (12th February 2019) - Haberer, Jessica E; Bwana, Bosco M; Orrell, Catherine; Asiimwe, Stephen; Amanyire, Gideon; Musinguzi, Nicholas; Siedner, Mark J; Matthews, Lynn T; Tsai, Alexander C; Katz, Ingrid T; Bell, Kathleen; Kembabazi, Annet; et al.
Abstract: Introduction: The success of universal antiretroviral therapy (ART) access and aspirations for an AIDS‐free generation depend on high adherence in individuals initiating ART during early‐stage HIV infection; however, adherence may be difficult in the absence of illness and associated support. Methods: From March 2015 to October 2017, we prospectively observed three groups initiating ART in routine care in Uganda and South Africa: men and non‐pregnant women with early‐stage HIV infection (CD4 > 350 cells/μL), pregnant women with early‐stage HIV infection and men and non‐pregnant women with late‐stage HIV infection (CD4 < 200 cells/μL). Socio‐behavioural questionnaires were administered and viral loads were performed at 0, 6 and 12 months. Adherence was monitored electronically. Results: Adherence data were available for 869 participants: 322 (37%) early/non‐pregnant, 199 (23%) early/pregnant and 348 (40%) late/non‐pregnant participants. In Uganda, median adherence was 89% (interquartile range 74 to 96) and viral suppression was 90% at 12 months; neither differed among groups ( p > 0.72). In South Africa, median adherence was higher in early/non‐pregnant versus early/pregnant or late/non‐pregnant participants (76%, 37%, 52%; p < 0.001), with similar trends in viral suppression (86%, 51%, 79%; p < 0.001). Among early/non‐pregnant individuals in Uganda, adherence was higher with increasing age and lower with structural barriers; whereas in South Africa, adherence was higher with regular income, higher perceived stigma and use of other medications, but lower with maladaptive coping and cigarette smoking. Discussion: ART adherence among non‐pregnant individuals with early‐stage infection is as high or higher than with late‐stage initiation, supporting universal access to ART. Challenges remain for some pregnant women and individuals with late‐stage infection in South Africa and highlight the need for differentiated care delivery.